Oral Health-Related Quality of Life in Patients With Chronic Respiratory Diseases—Results of a Systematic Review - Li, Simin; Ning, Wanchen; Wang, Wei; Ziebolz, Dirk; Acharya, Aneesha; Schmalz, Gerhard; Zhao, Jianjiang; Huang, Shaohong; Xiao, Hui (Frontiers in Medicine, 2022)
Background: Aim of this systematic review was to evaluate the oral health-related quality of life (OHRQoL) of patients with chronic respiratory diseases. Methods: A systematic literature search was performed based on PubMed, Medline, Web of Science and Scopus, using the search terms: "oral health-related quality of life" AND “respiratory disease” OR “lung” AND "oral health-related quality of life". Full-text articles published until 30th of June 2021 and reporting any OHRQoL measurement in children or adults with a chronic respiratory disease or condition were included and analysed qualitatively. Results: Seven out of 44 studies were included, of which four examined adults and three investigated children. The respective diseases were chronic obstructive pulmonary disease (COPD, n=2), sleep apnoea (n=2), severe asthma (n=1), cystic fibrosis (n=1) and lung transplantation (n=1). Four studies confirmed a worse OHRQoL in respiratory diseased group, compared to healthy controls. The overall OHRQoL was reduced in the included studies. Oral health, health-related quality of life and disease-related parameters were rarely examined with regard to OHRQoL. Conclusions: Patients with chronic respiratory diseases show a reduced OHRQoL. Oral health should be fostered in these individuals to support their OHRQoL. Keywords: oral health; oral health-related quality of life; respiratory disease, lung